Impact of acute kidney injury on patient outcome in out‐of‐hospital cardiac arrest: a prospective observational study. Issue 8 (16th June 2016) - Beitland, S.; Nakstad, E. R.; Stær‐Jensen, H.; Drægni, T.; Andersen, G. Ø.; Jacobsen, D.; Brunborg, C.; Waldum‐Grevbo, B.; Sunde, K.
Abstract : Background: Kidney disease after out‐of‐hospital cardiac arrest (OHCA) is incompletely described. We examined the occurrence of acute kidney injury (AKI) in OHCA patients and impact of AKI, with or without renal replacement therapy (RRT), on 6‐month mortality and neurological outcome. Methods: Prospective study at Oslo University Hospital, Oslo, Norway. Adult resuscitated comatose OHCA patients treated with targeted temperature management at 33°C for 24 h were included. AKI and chronic kidney disease (CKD) were classified according to the Kidney Disease Improving Global Outcomes (KDIGO) guidelines. Main outcomes were 6‐month mortality and good neurological outcome defined as Cerebral Performance Category 1–2. Results: Among 245 included patients (84% males, mean age 61 years), 11 (4%) had previously known CKD and 112 (46%) developed AKI. Overall 6‐month outcome revealed that 112 (46%) died and 123 (50%) had good neurological outcome. Compared with no kidney disease, the presence of AKI was significantly associated with 6‐month mortality (odds ratio (OR) 3.17, 95% confidence interval (CI) 1.95–5.43, P < 0.001) and good neurological outcome (OR 0.28, 95% CI 0.16– 0.48, P < 0.001). Six‐month mortality (50 vs. 61%, P = 0.401) and frequency of good neurological outcome (44 vs. 35%, P = 0.417) were not statistically different in AKI patients with or without RRT, also after excluding patients where RRT was withheld due to futility. Conclusions: Kidney disease occurred in about half of patients successfully resuscitated from OHCA. Presence of AKI, but not RRT, was associated with unfavourable 6‐month outcome.